2001
DOI: 10.1002/1097-0215(200002)9999:9999<::aid-ijc1082>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

The role of caspase 3 in producing cytokeratin 19 fragment (CYFRA21-1) in human lung cancer cell lines

Abstract: The CYFRA 21‐1 assay, which detects cytokeratin 19 (CK19) fragment, is widely used as a tumor marker for lung cancer, particularly non‐small cell lung cancer. However, the reason that some lung cancer cell lines release CYFRA 21‐1 in culture supernatants and others do not remains unclear. We hypothesized that the release of CYFRA 21‐1 might be related to the expression of CK19 and caspase 3. In order to prove this, the quantities of mRNA for CK19 were evaluated by the competitive reverse transcriptase‐polymera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(35 citation statements)
references
References 22 publications
1
33
0
1
Order By: Relevance
“…Using MCF-7 cells, Sheard et al revealed TPS (i.e., CK18) and Cyfra 21-1 (CK19) are abundantly released during apoptosis and the release precedes DNA fragmentation (Sheard et al, 2002). We also observed mRNA expression of CK19 is essential in Cyfra 21-1 formation and caspase 3 plays an important role in producing Cyfra 21-1 in human lung cancer cell lines (Dohmoto et al, 2000;Dohmoto et al, 2001). Kramer described that large amounts of CK18 are released into extracellular space during necrosis induced by oligomycin, and that release of CK18 is a marker of epithelial cell death and not a marker of apoptosis (Kramer et al, 2004).…”
Section: Mechanisms Of Cytokeratin Releasesupporting
confidence: 51%
See 2 more Smart Citations
“…Using MCF-7 cells, Sheard et al revealed TPS (i.e., CK18) and Cyfra 21-1 (CK19) are abundantly released during apoptosis and the release precedes DNA fragmentation (Sheard et al, 2002). We also observed mRNA expression of CK19 is essential in Cyfra 21-1 formation and caspase 3 plays an important role in producing Cyfra 21-1 in human lung cancer cell lines (Dohmoto et al, 2000;Dohmoto et al, 2001). Kramer described that large amounts of CK18 are released into extracellular space during necrosis induced by oligomycin, and that release of CK18 is a marker of epithelial cell death and not a marker of apoptosis (Kramer et al, 2004).…”
Section: Mechanisms Of Cytokeratin Releasesupporting
confidence: 51%
“…Furthermore, a specific inhibitor of caspase 3 efficiently inhibited the release of Cyfra 21-1 into culture supernatants. Based on these observations we concluded that caspase 3 plays an important role in the production of Cyfra 21-1 in lung cancer cell lines (Dohmoto et al, 2001). Pujol et al evaluated Cyfra 21-1 and TPS in 405 lung cancer patients (91 SCLC and 314 NSCLC) and in 59 patients with non-malignant lung diseases.…”
Section: Circulating Cytokeratin-related Molecules and Their Biologicmentioning
confidence: 70%
See 1 more Smart Citation
“…They are classified into two types: acidic type I (CK9-CK20) and basic type II (CK1-CK8) [99]. Epithelial cells are targets of caspase-mediated proteolysis during apoptosis [100]. CK19 is cleaved by caspase 3 and soluble fragments (CYFRA 21-1), released into extracellular space, have been detected in sera of cancer patients [62,101] and reportedly do not correlate with that of full-length CK19 mRNA [62].…”
Section: Cytokeratin 19mentioning
confidence: 99%
“…The 14-3-3 protein is externalized to the medium by epithelial cell types, although the function of this protein in V. vulnificus infectious disease remains to be clarified. PRX II belongs to a ubiquitous PRX family, which has been associated with multiple functions, including enhancing natural killer cell activity (29), increasing cell resistance to oxidative stress (30), protecting erythrocytes against oxidative stress (31), and anti-HIV activity (32). However, the function of PRX II in the context of V. vulnificus infectious disease also requires clarification.…”
Section: Discussionmentioning
confidence: 99%